2023
DOI: 10.1128/spectrum.02113-22
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study of Companion Animal-Derived Multidrug-Resistant Escherichia coli in Hangzhou, China

Abstract: MDR Escherichia coli are considered a global threat because of the decreasing options for antimicrobial therapy. Companion animals could be a reservoir of MDR E. coli , and the numbers of pets and households owning pets in China are booming.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…A recent study conducted in healthy animals in Hangzhou (China) showed high percentages of MDR in E. coli strains isolated from dogs and cats, 41% and 30%, respectively [42]. However, studies addressing the situation of AMR and MDR in asymptomatic companion animals are scarce in the EU, as the main focus is usually on diseased animals.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study conducted in healthy animals in Hangzhou (China) showed high percentages of MDR in E. coli strains isolated from dogs and cats, 41% and 30%, respectively [42]. However, studies addressing the situation of AMR and MDR in asymptomatic companion animals are scarce in the EU, as the main focus is usually on diseased animals.…”
Section: Discussionmentioning
confidence: 99%
“…The ARGs were detected by Abricate v1.0.1 with the ResFinder ( 51 ) database. Only ARGs with similarity greater than 95% and coverage greater than 98% were identified ( 52 ). Each identified ARG was manually classed into different antimicrobial categories to which they belong.…”
Section: Methodsmentioning
confidence: 99%
“…Veterinary drugs (VDs) play a crucial role in the healthcare of livestock , as they are prescribed to cure animal diseases and control infections (Mouiche et al, 2019).These agents have been shown to improve animal production efficiency, enhance livestock product quality, and contribute to the maintenance of ecological balance (Teng et al, 2023) . Studies have demonstrated that the use of VDs in animal farming can increase feeding and performance, resulting in higher agricultural productivity (Baars, 1984).However, the benefits of drug administration to farm animals used for food production are also accompanied by the risks associated with drug residue in the edible parts of animal tissues (Moreno et al, 2017).As highlighted in various sources, the illegal and abusive usage of VDs can result in both short-term and long-term public health hazards (Canton et al, 2021).These drugs can be accumulated in animal tissue and the residues can cause severe risks to human health, such as toxic effects and allergic reactions.…”
Section: Introductionmentioning
confidence: 99%